Peningkatan Hasil Belajar Siswa pada Pelajaran Pendidikan Agama Islam melalui Model Discovery Learning - Isna Ayu Nurmaidah; Dedih Surana; Huriah Rachmah (Jurnal Riset Pendidikan Agama Islam, 2023)
Abstract. The research was conducted at SDN Babakan Sukamulya class IV with the aim of knowing whether there was an increase in student learning outcomes through model discovery learning on Islamic Religious Education subjects and Budi Pekerti (PAIBP). This study uses a quantitative approach, method quasi experiment with a design shape Nonequivalent Control Group Design. The results of research in the experimental class (IVB) and control class (IVA) shows 1) The learning process in the experimental class seen from the preparation of the Learning Implementation Plan (RPP) of 92.30% components are complete, while 7.69% sub components are incomplete. Implementation learning results in a percentage of 90.4% in the very category satisfactory out of 19 sub-indicators with a score of 95, while 2 sub-indicatorsothers get a score of 10 with a percentage of 9.52%; 2) Learning outcomes students experienced an increase after being given the model treatment discovery learning including cognitive with an average before (58.23) after (90.77), affective before (71.9) after (92.45), psychomotor before (73.8) after (86.68). Differences in learning outcomes between control classes and experimentally proven by test analysist, cognitive t count (6,874) > t table (2.018), affective t count (10,145) > t table (2.018), psychomotor t count (3,002) > t table (2.018), so it is concluded that the model discovery learning can improve student learning outcomes PAIBP lessons in class IV; 3) Factors supporting the learning process influenced by school factors, RPP, LKPD, assessment instruments, model sused. The inhibiting factor is the need for adaptation regarding the model learning used as well as field conditioning is required separation between the experimental class and the control class. Abstrak. Penelitian dilakukan di SDN Babakan Sukamulya kelas IV bertujuan untuk mengetahui adanya peningkatan hasil belajar siswa melalui model discovery learning pada mata pelajaran Pendidikan Agama Islam dan Budi Pekerti (PAIBP). Penelitian ini menggunakan pendekatan kuantitatif, metode quasi eksperimen dengan bentuk desain Nonequivalent Control Grup Desain. Hasil penelitian di kelas eksperimen (IVB) dan kelas kontrol (IVA) menujukkan 1) Proses pembelajaran di kelas eksperimen dilihat dari penyusunan Rencana Pelaksanaan Pembelajaran (RPP) sebesar 92,30 % komponen sudah lengkap, sedangkan 7,69% sub komponen belum lengkap. Pelaksanaan pembelajaran mengahasilkan persentase sebesar 90,4% dengan kategori sangat memuaskan dari 19 sub indikator dengan skor 95, sedangkan 2 sub indikator lainnya mendapatkan skor 10 dengan peresentase sebesar 9,52%; 2) Hasil belajar siswa mengalami peningkatan setelah diberi perlakuan model discovery learning diantaranya kognitif dengan rata-rata sebelum (58,23) setelah (90,77), afektif sebelum (71,9) setelah (92,45), psikomotor sebelum (73,8) setelah (86,68). Perbedaan hasil belajar antara kelas kontrol dan eksperimen dibuktikan dengan analisis uji t, ranah kognitif t hitung (6,874) > t tabel (2,018), ranah afektif t hitung (10,145) > t tabel (2,018), ranah psikomotor t hitung (3,002) > t tabel (2,018), jadi, disimpulkan bahwa model discovery learning dapat meningkatkan hasil belajar siswa pada mata pelajaran PAIBP di kelas IV; 3) Faktor pendukung proses pembelajaran dipengaruhi oleh faktor sekolah yaitu RPP, LKPD, Instrument penilaian, model yang digunakan. Faktor penghambat yaitu perlunya adaptasi mengenai model pembelajaran yang digunakan serta pengkondisian lapangan diharuskan adanya pemisahan antara kelas eksperimen dan kelas kontrol.